Rereading qahal as Deuteronomist history works: Literal and ideological criticism approach - Napitupulu, Pieter Anggiat; Santoso, Agus; Putrawan, Bobby Kurnia (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2022)
Some biblical scholars understand Deuteronomy to be the end of the Pentateuch. Before the nation of Israel became a confederate system, the socio-political reality could usually be seen in the composition, interaction, and behavior of relationships in society, which were assumed to be political elements. The Israeli confederation which is like the ambition centered on Yahweh is what the author refers to as Israel's